Petrological and Geochemical Comparison of Rodingites from Kimi -Evia island with outcrops from adjacent regions - Karkalis, Christos; Magganas, Andreas; Koutsovitis, Petros (Bulletin of the Geological Society of Greece, 2019)
The present study is focused on the geochemical and petrological comparison between rodingites from the Kimi region in Central Evia (Greece) with those from East and West Othris, as well as with rodingites from Skyros island. Based upon their whole rock geochemical and petrographical data it is suggested that rocks from Skyros island and Kimi-Evia display similar features. Kimi-Evia and Skyros rodingites are characterized by their highly comparable REE patterns with significant LREE enrichments. This is most likely attributed to the effects of carbonic rich fluids, enhancing the transfer of REE via CO3-2 ligands. The West Othris rodingites display similar MREE and HREE patterns with the least fractionated rodingites from Kimi-Evia and Skyros, whereas the LREE are significantly depleted. The East Othris rodingites differ from all other rodingite occurrences, since they exhibit much lower ΣREE contents. Rodingitization in all studied areas was associated with serpentinization processes and was evolved in several metasomatic stages, in which vesuvianite was formed during the last episodes at relatively low temperatures.